Individual Learning Plan for Teaching English to Learners with Dyslexia - Laslettová, Anna (Univerzita Pardubice, 2017)
The bachelor thesis is focused on the creation and use of the Individual Learning Plan for the teaching English to a learner with dyslexia. The thesis is divided into two parts. Problems of dyslexia, its definitions, history and research, approaches and methods to overcome it, are analysed in the theoretical part which ends with the main focus on the Curriculum and the documents belonging to it in the connection with the Individual Learning Plan. The second part of the bachelor thesis is focused on the practical possibilities in use of the Individual Learning Plan in the real school environment. The aim is to ascertain if the backup given to both, the learner and the teacher is sufficient and what is the real function of the Individual Learning Plan in practice.
Individuální vzdělávací plán pro výuku anglického jazyka žáků s dyslexií
Keywords: dyslexie; individuální vzdělávací plán; individual learning plan; dyslexia